Solvability in the Sense of Sequences for Some Non-fredholm Elliptic Problems - Volpert, Vitaly; Vougalter, Vitali (Discontinuity, Nonlinearity, and Complexity, 2026)
We establish solvability in the sense of sequences in the appropriate H2 spaces for certain linear nonhomogeneous elliptic problems involving Schrödinger type operators without Fredholm property using the technique developed in our preceding work [23]. We show the existence of bounded solutions for certain nonlinear Lippmann-Schwinger equations.